Gender-based differences in the effectiveness of antihypertensive therapy with losartan compared with enalapril (Bangladesh Journal of Medical Science, 2021)
Objective: Today there is a limited number of gender-based characteristics of the enalapril and losartanadministration in order to correct blood pressure in patients with arterial hypertension.The aim ofthe study was to compare the effectiveness of enalapril and losartan for blood pressure correcting inpatients with arterial hypertension (AH), depending on gender.Materials and methods: The studywas carried out in 2019 at Military Hospital 175 in Ho Chi Minh city, Vietnam. To achieve this goal,100 people were included in the study (50 females in the menopause and 50 males) with grade I-IIarterial hypertension aged 50 to 60 years. Patients with hypertension were divided into the followinggroups: group 1A – 25 males, who received enalapril 20 mg/d and 12.5 mg/d hydrochlorothiazideonce per day as antihypertensive therapy; group 1B – 25 males, who received losartan 50 mg/d andhydrochlorothiazide 12.5 mg/d once per day; group 2A – 25 females, who received enalapril 20 mg/dand hydrochlorothiazide 12.5 mg/d once per day; group 2B – 25 females, who received losartan 50mg/d and hydrochlorothiazide 12.5 mg/d once per day. The follow-up was 12 weeks.Results anddiscussion: The study showed that antihypertensive therapy with losartan is more effective in femalescompared with enalapril, as evidenced by a significant SBP decrease by 21.1% (p